The Yield-Forming Role of Nitrogen in Rice in the Growing Seasons with Variable Thermal Conditions - Jianwei Zhang; Yan Zhou; Longmei Wu; Lei Xu; Cong Xu; Dong Liang; Yanfeng Ding; Yongchun Zhang; Jidong Wang; Ganghua Li (Agronomy, 2023)
A reduced basal and increased topdressing fertilizer rate (RBIT) can usually increase rice yield, but whether this practice alleviates the impact of poor weather on rice production is unknown. Thus, the effect of three integrated RBIT treatments (RBITs, including RBIT alone, RBIT in combination with straw incorporation (RBITS) or a reduced fertilizer rate (RBITR)) on rice growth and nutritional status under different weathers was investigated in a 9-year experiment. Conventional fertilization (CF) was the control. We found that daytime temperature and light (DTL) after heading were the main meteorological factors limiting rice yield increases. RBITs did not affect rice yield under High-DTL, compared with CF, but RBITS significantly increased rice yield under Low-DTL. Compared with High-DTL, the positive effect of RBIT and RBITR on the N concentration and proportion in vegetative organs under Low-DTL was higher than the K concentration in vegetative organs, but RBITS showed the opposite trend. Regression analysis indicated that the harvest index had stronger correlations with the N concentration (negative), K concentration (positive), and N/K (negative) in vegetative organs under Low-DTL than under High-DTL. Our findings suggested that RBITS could improve rice adaptability to daytime temperature and light changes after heading by balancing crop nutritional status (N/K).